MEMS Modulator-Based Mid-Infrared Laser Heterodyne Radiometer for Atmospheric Remote Sensing - Xue, Zhengyue; Shen, Fengjiao; Li, Jun; Liu, Xiaohai; Wang, Guishi; Liu, Kun; Gao, Xiaoming; Chen, Weidong; Tan, Tu (Frontiers in Physics, 2022)
The performance of a mid-infrared laser heterodyne radiometer (MIR-LHR) based on a micro-electro-mechanical system (MEMS) mirror is demonstrated in ground-based solar occultation mode. A MEMS mirror is employed as an alternative modulator to the traditional mechanical chopper. High-resolution (∼0.0024 cm−1) transmission spectrum near 3.93 μm was obtained for atmospheric observation of N2O absorption. Operation of the MIR-LHR with laser-induced shot-noise limited performance was analyzed and experimentally achieved. The laser heterodyne spectrum obtained is consistent with Fourier-transform infrared (FT-IR) spectrometer and atmospheric transmission modeling. Compared to the traditional chopper, the MEMS mirror is smaller, lighter and lower power consumption which makes the system more stable and compact. The reported MIR-LHR in this article has great potential in aircraft instruments and satellite payloads.